Is there a role for PET/CT parameters to differentiate thyroid cartilage invasion from penetration?. Issue 2 (February 2016) - Kendi, A. Tuba; Corey, Amanda; Magliocca, Kelly R.; Galt, James R.; Zhang, Chao; Chen, Zhengjia; Higgins, Kristin; Beitler, Jonathan J.; Wadsworth, J. Trad; El-Deiry, Mark W.; Schuster, David M.; Saba, Nabil F.; et al.
Abstract: Background: Assessment of thyroid cartilage invasion (tumor extension through inner cortex) and thyroid cartilage penetration (tumor involving both the inner and outer cortices of thyroid cartilage) may be challenging with CT (Computed Tomography) and MR imaging (Magnetic Resonance Imaging). Positron Emission Tomography/Computed Tomography (PET/CT) is a non invasive imaging modality that provides both anatomic and metabolic information. Quantitative data obtained from PET/CT, also known as PET/CT parameters, include maximum, mean or peak standardized uptake values (SUVmax, SUVmean, SUVpeak), metabolic tumor volume (MTV), total lesion glycolysis (TLG), standardized added metabolic activity (SAM) and normalized standardized added metabolic activity (NSAM). Our aim was to examine if FDG PET/CT parameters could differentiate thyroid cartilage invasion from penetration. Methods: 50 patients who underwent PET/CT before laryngectomy for squamous cell carcinoma of the larynx, had SUVmax, SUVmean, SUVpeak, TLG, MTV, SAM and NSAM calculated on a dedicated workstation. Univariate and multivariate analysis was performed. ROC analysis was used to determine the ability of PET/CT parameters to predict pathologically proven thyroid cartilage invasion or penetration. Results: Of the 50 patients, 50% (25/50 patients) had history of prior radiation therapy. Among the previously irradiated group, 24% had thyroid cartilage invasion and penetration. 8% of the patients in this group had thyroid cartilage invasion only. Among the non-irradiated group, 76% had thyroid cartilage invasion and penetration, 8% had thyroid cartilage invasion without penetration. ROC analysis revealed that none of the PET/CT parameters had enough power to predict thyroid cartilage penetration, but TLG, MTV and SAM had enough power to predict thyroid cartilage invasion in non-irradiated patients. TLG, MTV, SAM and NSAM had enough power to predict thyroid cartilage invasion and penetration in irradiated group. Conclusion: TLG, MTV and SAM have enough power to predict thyroid cartilage invasion and penetration in irradiated patients. PET/CT parameters do not have enough potential to differentiate thyroid cartilage invasion from penetration.